2001
DOI: 10.1097/00002060-200107000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Resistance Muscle Strength Training of Hospitalized Frail Elderly

Abstract: A carefully monitored program of progressive resistance muscle strength training to regain muscle strength is a safe and possibly effective method for frail elderly recuperating from acute illnesses. A randomized control study is needed to examine the degree to which progressive resistance muscle strength training offers advantages, if any, over routine posthospital care that includes traditional low-intensity physical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0
7

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 22 publications
7
27
0
7
Order By: Relevance
“…Programs tailored for rehabilitation after acute medical illness or for chronic musculoskeletal conditions have been proven to be effective in older populations (34). Cardiac rehabilitation programs have shown physiological benefits which occurred regardless of age (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Programs tailored for rehabilitation after acute medical illness or for chronic musculoskeletal conditions have been proven to be effective in older populations (34). Cardiac rehabilitation programs have shown physiological benefits which occurred regardless of age (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies that included physical therapy for older adults posthospitalization reported positive results in their ability to perform instrumental ADL and walk [21][22]. Another study that used a progressive resistance muscle strengthening program also reported improvements in function and ambulation [23]. The patients who were interviewed expressed the belief that exercise, particularly walking and strengthening, would be beneficial especially if it was started just prior to hospital discharge or shortly after being discharged to home.…”
Section: Qualitative Response Number Of Patientsmentioning
confidence: 99%
“…(James, 1993;Mills, 1994;Meuleman et al, 2000;Sullivan et al, 2001). 한편 산림 걷기 운동도 다양한 환경적 조건과 함께 울퉁불퉁하고, 오르내림의 경 사도가 다양하고, 다양한 신체적 자세변화로 인하여 균형 과 중력부하를 견뎌야 하는 산길이 자연스럽게 근육과 건, 관절의 고유감각 수용기를 발달시켰고 (Choi, 2011;Lord et al, 1995;Shumway-Cook and Woollacott, 2007), 신 체분절간의 생체 역학적인 평형성과 신경근과 사지간의 공동작용을 포함한 운동 처리과정을 원활하게 하여 동적 평형성을 향상시켰다 (Kelso and Tuller, 1984;Newell, 1986).…”
Section: 보행박자에 있어 집단과unclassified